Comparison of the Implementation of Good Faith in Indonesia, China, and Japan: Building Legal Harmonization - Fajar Rachmad Dwi Miarsa; M. Zamroni; Kunihiko Yoshida (SASI)
Introduction: The principle of good faith in contract law serves as a guiding principle for fairness, predictability, and trust in legal transactions. This principle, while universally recognized, finds varying interpretations and applications across different legal systems, reflecting the influence of their unique legal traditions, historical contexts, and legal cultures.